2007
DOI: 10.1007/s11095-007-9350-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Solid Maltose Microneedles and their Use for Transdermal Delivery

Abstract: Maltose microneedles were characterized and shown to create microchannels in the skin, which were also characterized and shown to improve the transdermal delivery of NH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 20 publications
10
123
0
1
Order By: Relevance
“…21) Kolli and Banga reported that micropiles with a length of 500 mm are applied to the skin and pressed using a finger with a pressure of approximately 0.35-0.5 N, the whole micropile is not inserted into the skin. 22) The usefulness of SDMP was studied with macromolecular compounds such as insulin, 23) low molecular weight heparin (LMWH) 24) and erythropoietin (EPO) 25) from both pharmacokinetic and pharmacodynamic aspects. From these studies, SDMPs were shown to be an effective TDDS for the percutaneous absorption of hydrophilic macromolecular drugs.…”
mentioning
confidence: 99%
“…21) Kolli and Banga reported that micropiles with a length of 500 mm are applied to the skin and pressed using a finger with a pressure of approximately 0.35-0.5 N, the whole micropile is not inserted into the skin. 22) The usefulness of SDMP was studied with macromolecular compounds such as insulin, 23) low molecular weight heparin (LMWH) 24) and erythropoietin (EPO) 25) from both pharmacokinetic and pharmacodynamic aspects. From these studies, SDMPs were shown to be an effective TDDS for the percutaneous absorption of hydrophilic macromolecular drugs.…”
mentioning
confidence: 99%
“…Therefore, to reach an effective blood concentration, the therapeutic efficacy of drug should be improved by increasing drug administration. [21] Kolli and Banga [22] show that the plasma drug concentration reaches its maximum when using microneedles as compared to passive 95 delivery.…”
mentioning
confidence: 99%
“…Therefore even in the case of metallic micropiles, the length was designed to be Ͼ500 mm. 28) When micropiles with a length of 500 mm are applied to the skin, it was pressed using a finger with a pressure of approximately 0.35-0.5 N. 29) In our study, the SDMA chip was administered to both rat and dog abdominal skin using the pressure of the fingers. The skin was at first pulled up with two fingers.…”
Section: Discussionmentioning
confidence: 93%
“…A coin was pressed against one side of the skin fold, and SDMA was inserted on the other side of skin by pressing with a finger. Both pressing force was adjusted to 0.3-0.5 N. 29) Using this method, SDMA was easily inserted into the skin and a good absorption enhancing effect was obtained in both rat and dog experiments.…”
Section: Discussionmentioning
confidence: 99%